2013
DOI: 10.3402/gha.v6i0.19201
|View full text |Cite
|
Sign up to set email alerts
|

Health, wellbeing, and disability among older people infected or affected by HIV in Uganda and South Africa

Abstract: ObjectiveTo describe and compare the health status, emotional wellbeing, and functional status of older people in Uganda and South Africa who are HIV infected or affected by HIV in their families.MethodsData came from the general population cohort and Entebbe cohort of the Medical Research Council/Uganda Virus Research Institute, and from the Africa Centre Demographic Information System through cross-sectional surveys in 2009/10 using instruments adapted from the World Health Organization (WHO) Study on Global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…It has long been known that women are particularly vulnerable to both depression and HIV, and it seems likely, given that women carry a disproportioned burden of caregiving in most low and middle income settings, that the effects of depression extend to impact on the family and the quality of care, rather than being limited to the individual. In earlier analyses (Nyirenda et al, 2013) we found that 2 in 3 of the older people were care-givers to at least one adult offspring or child; and as seen in other studies, a higher proportion of older people are main care-givers to HIV-infected adults and to children they leave behind orphaned (Hill et al, 2008; Ssengonzi, 2007; Schatz, 2007). Here we show a strong association between care-giving, especially to adults, and having a depressive episode.…”
Section: Discussionsupporting
confidence: 65%
“…It has long been known that women are particularly vulnerable to both depression and HIV, and it seems likely, given that women carry a disproportioned burden of caregiving in most low and middle income settings, that the effects of depression extend to impact on the family and the quality of care, rather than being limited to the individual. In earlier analyses (Nyirenda et al, 2013) we found that 2 in 3 of the older people were care-givers to at least one adult offspring or child; and as seen in other studies, a higher proportion of older people are main care-givers to HIV-infected adults and to children they leave behind orphaned (Hill et al, 2008; Ssengonzi, 2007; Schatz, 2007). Here we show a strong association between care-giving, especially to adults, and having a depressive episode.…”
Section: Discussionsupporting
confidence: 65%
“…These findings are consistent with those of previous studies that have reported that women are more predisposed to the adverse effects of occupational stressors and also experience difficulties in acquiring emotional support that lead to psychological distress [21]. We also found an association between the level of education and social participation, which is similar to the findings of other studies [22]. The illiterate patients exhibited higher scores than did the literate patients.…”
Section: Discussionsupporting
confidence: 93%
“…120 Similarly, in Nairobi slums, an estimated 12% of urban adult low-income Kenyans have HIV/AIDS 78 and 10% of adults aged between 40 and 54 years have diabetes. 76 Cohort studies in Uganda and South Africa document HIV-NCD convergence; 121122123124 psychological distress increases among those with multiple conditions and NCDs are lower among older adults without HIV, which might result from routine antiretroviral therapy. 125 More epidemiological studies are needed that document the co-occurrence of diabetes and HIV within the same individuals; however, anthropological research shows that people with HIV are developing diabetes and this poses complex medical issues, including the prioritisation of HIV care over diabetes care because of international donor stipulations on AIDS funding.…”
Section: Syndemic Poverty Diabetes and Hiv In Lmicsmentioning
confidence: 99%